GIS METHODOLOGICAL APPROACH TO DEVELOPING AND FORMING A VISUAL IMAGE OF DOWNTOWN AMMAN - Al Fahmawee Emad Al Dein Hasan (Architecture and Engineering, 2021)
Introduction: Amman’s growth expansion was shaped by its topography (valleys and hills), which generated a special character and patterns of the urban form. The city was built on seven hills, which are connected by steep stairs that serve as pathways to the downtown core. The rapid urbanization caused by uncontrolled population growth, as well as random and unplanned formations that were far from following any kind of aesthetic, resulted in the expansion of the center towards the surrounding seven hills. The continuous intersection of these hills caused their boundaries to blur and melt. As a result of the intense transformation, which is causing the hills’ appearance to become more uniform, their continuing overlap may completely destroy the unique character and imageability of downtown Amman. Methods: This research made use of topographical context analysis and the Geographical Information System (GIS) as well as its 3D modeling function to identify the optimal visibility and viewing angle when looking from the valley towards the hills and between the hills. Results and discussion: We identified the main vistas, i.e., highly significant views, which could subsequently be adopted as the locations for proposing landmark scenarios via 3D model GIS analysis. The projection process helped determine the significant views from the valley towards the hills and between the hills. Overall, three scenarios were proposed for the landmarks, out of which, the best one was chosen. It corresponds to the topographical analysis and the community needs, depends upon the local context and urban fabric, and is optimal for decision-making.